Efficiency of the newly proposed practice guideline of catheter traction after transurethral resection of prostate (TURP) in patients with benign prostatic hyperplasia (BPH) - Seewilai, Taweepon; Amornvesukit, Teerapon; Jitpraphai, Siros; Chotikawanich, Ekkarin; Taweemonkongsap, Tawatchai; Leewansangtong, Sunai; Nualyong, Chaiyong (Insight Urology, 2019)
Objective: To study the efficiency of catheter traction in patients with BPH after TURP, according to the newly proposed practice guideline. Material and Method: A single-center randomized controlled trial. Randomization was undertaken using computer generated tables in order to allocate treatments. Sixty patients with BPH after TURP were randomized to receive catheter traction, according to the newly proposed or routine practice guidelines. Newly proposed practice guideline of catheter traction in patients with BPH after TURP (See full article). The efficiency of the guideline was evaluated by 1) Postoperative clot retention 2) Re-catheter traction 3) Re-continuous bladder irrigation (CBI) 4) Hematocrit decrease after surgery 5) Length of hospital stay. Result: Sixty patients (newly proposed guideline n=30; routine traction n=30) were randomized. There was no significant difference in demographic and preoperative data between the two groups. Postoperative clot retention rate, re-catheter traction rate, re-CBI rate and mean hematocrit decrease were not different between the two groups, [(0% vs 3.3%), (0% vs 3.3%), (6.7% vs 10%), p=1.0], [3.52 (2.99) vs 3.43 (2.95), p=0.91] respectively. Length of hospital stay was statistically different in the two groups (3.57 vs 4.37, p=0.04). Conclusion: The newly proposed practice guideline is safe and efficient. It could be applied in routine practice.